TREATMENT TACTICS FOR PURULENT-NECROTIC LESIONS OF THE FOOT IN PATIENTS WITH DIABETES MELLITUS - Musashaykhov X.T; Ikramova F.D; Vokhidova O.SH (Bright Mind Publishing, 2025)
Purulent-necrotic lesions of the foot remain one of the most severe complications of diabetes mellitus, often leading to disability and high rates of lower limb amputation. The comprehensive treatment of this pathology requires a multidisciplinary approach aimed at correcting metabolic disorders, improving microcirculation, controlling infection, and accelerating wound healing. The study emphasizes the importance of combined methods, including rational antibiotic therapy, surgical interventions, local treatment of wounds, and physiotherapeutic procedures. Special attention is given to innovative techniques such as intra-arterial and lymphotropic administration of drugs, which provide high concentrations of antibiotics directly in the affected tissues and lymphatic system. The obtained results demonstrate that an integrated approach significantly reduces the frequency of amputations, improves treatment outcomes, and enhances the quality of life in patients with diabetic foot syndrome complicated by purulent-necrotic processes.
Keywords: diabetes mellitus, diabetic foot, purulent-necrotic lesions